“Finding an Emotional Face” Revisited: Differences in Own-Age Bias and the Happiness Superiority Effect in Children and Young Adults - Zsido, Andras N.; Arato, Nikolett; Ihasz, Virag; Basler, Julia; Matuz-Budai, Timea; Inhof, Orsolya; Schacht, Annekathrin; Labadi, Beatrix; Coelho, Carlos M. (Frontiers in Psychology, 2021)
People seem to differ in their visual search performance involving emotionally expressive faces when these expressions are seen on faces of others close to their age (peers) compared to faces of non-peers; known as the own-age bias. This study sought to compare search advantages in angry and happy faces detected on faces of adults and children on a pool of children (N=77, Mean age=5.57) and adults (N=68, Mean age=21.48). The goals of this study were to 1, examine the developmental trajectory of expression recognition, and 2, examine the development of an own-age bias. Participants were asked to find a target face displaying an emotional expression among eight neutral faces. Results showed that children and adults found happy faces significantly faster than angry and fearful faces regardless of it being present on the faces of peers or non-peers. Adults responded faster to the faces of peers regardless of the expression. Further, while children detected angry faces significantly faster compared to fearful ones, we found no such difference in adults. In contrast, adults detected all expressions significantly faster when they appeared on the faces of other adults compared to the faces of children. In sum, we found evidence for development in detecting facial expressions and also an age-dependent increase in own-age bias. We suggest that the happy face could have an advantage in visual processing due to its importance in social situations and its overall higher frequency compared to other emotional expressions. Although we only found some evidence on the own-age bias, using peer or non-peer faces should be a theoretical consideration of future research because the same emotion displayed on non-peers’ compared to peers’ faces may have different implications and meanings to the perceiver.